Proprioception and resistance band training on injury prevention in gymnasts - Murgia, C. J. (Research Quarterly for Exercise and Sport, 2009)
Purpose: The purpose of this study was to examine effects of proprioception and resistance band training on inferior extremity joint kinesthesia, postural sway, and initial injury occurrence in gymnasts.